Advance care planning supported by clinicians trained for end-of-life care in Japanese nursing homes. Issue 2 (1st June 2012) - Nishikawa, M; Yokoe, Y; Miura, H; Hong, Y; Yoshida, Y; Shibasaki, M; Takamichi, K; Okumura, N; Endo, H; Nakashima, K
Abstract : In Japan, which has the highest rate of aging worldwide, the study of advance care planning (ACP) in nursing homes has only just begun. The aim of this study was to evaluate the utility of three clinical strategies on nursing home ACP, supported by trained ACP clinicians. The optimised strategy was to determine a policy on nursing home ACP, involving 1 doctor, 2 nurses, 1 social worker, and 1 facility director. The policy allowed residents and their families to opt out of undesired medical procedures. The proactive strategy was to conduct a lecture on ACP, involving 51 of 109 nursing home residents' families. We investigated the families' preferences regarding care of their dying relative in the nursing home before and after the lecture, even when death certificates were not promptly issued because many Japanese nursing homes have no full-time doctors. The reactive strategy was to perform a multi-occupational interview on ACP. Two nurses selected families of 21 frail residents with deteriorating physical conditions. The primary end-point was the number of residents who died in the nursing home in accordance with their wishes. The lecture significantly increased the number of families choosing terminal care in the nursing home (p <0.01). Intervention by these three strategies significantly increased the number of residents dying in the nursing home in accordance with their wishes (p <0.01). Intervention by these three strategies is useful and this presentation will demonstrate to other Japanese health professionals the technique of performing ACP in Japanese nursing homes.